Composition, sheet, and metal-clad laminate

The use of a composition combining fluororesin, inorganic particles, and organosiloxane in high-frequency printed wiring boards addresses the issues of water and moisture absorption, improving the boards' performance and reliability by reducing dielectric loss tangent.

JP2025054269AActive Publication Date: 2025-04-07DAIKIN INDUSTRIES LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2024164912
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2024-09-24
Publication Date
2025-04-07
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Existing high-frequency printed wiring boards face challenges with water absorption and moisture absorption, leading to appearance defects and increased dielectric loss tangent, which affects their performance.

Method used

A composition comprising a fluororesin, inorganic particles, and an organosiloxane is used to create a sheet that suppresses water and moisture absorption, thereby preventing defects and dielectric loss tangent increases.

Benefits of technology

The sheet effectively inhibits water and moisture absorption, maintaining the integrity of the printed wiring board and reducing dielectric loss tangent, thus enhancing its performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054269000001
    Figure 2025054269000001
  • Figure 2025054269000002
    Figure 2025054269000002
  • Figure 2025054269000003
    Figure 2025054269000003
Patent Text Reader

Abstract

To provide a composition that inhibits water absorption and moisture absorption, particularly a composition for obtaining a sheet in which an increase in dielectric loss tangent due to moisture absorption is suppressed, and also to provide a sheet and a metal-clad laminate, each obtained using the composition.SOLUTION: The present invention provides a composition that comprises a fluororesin, inorganic particles, and an organosiloxane, as well as a sheet and a metal-clad laminate, each obtained using the composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to compositions, sheets and metal clad laminates. [Background technology]

[0002] There is a demand for high-frequency printed wiring boards with small transmission loss. It is known that fluororesin films are used in such high-frequency printed wiring boards (Patent Document 1, etc.). In addition, Patent Documents 2 and 3 describe the use of fluororesin containing filler as a wiring board material.

[0003] Furthermore, Patent Document 4 discloses that a fluororesin composition in which spherical silica particles are blended with a fluororesin is used for a circuit board. Furthermore, Patent Document 5 describes a method of forming a polymer layer on a substrate using a dispersion containing a tetrafluoroethylene-based polymer and a liquid compound having a specific kinetic viscosity and boiling point to obtain a laminate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-8260 A [Patent Document 2] Japanese Patent Publication No. 63-259907 [Patent Document 3] Special Publication No. 2022-510017 [Patent Document 4] International Publication No. 2020 / 145133 [Patent Document 5] Patent Publication No. 2022-69962 Summary of the Invention [Problem to be solved by the invention]

[0005] The present disclosure has an object to provide a composition that suppresses water absorption and moisture absorption. It is also an object of the present disclosure to provide a composition that can provide a sheet that suppresses not only poor appearance due to water absorption but also an increase in dielectric tangent due to moisture absorption, and a sheet and a metal clad laminate using the same. [Means for solving the problem]

[0006] The present disclosure is a composition comprising a fluororesin, inorganic particles, and an organosiloxane. The inorganic particles are preferably inorganic particles containing silica as an essential component. The fluororesin is preferably a perfluoro-based fluororesin. The perfluoro-based fluororesin is preferably polytetrafluoroethylene (PTFE).

[0007] The silica is preferably spherical silica. The silica preferably has a dielectric loss tangent at 10 GHz of 0.0025 or less.

[0008] The inorganic particles are preferably coated with a silane coupling agent. The content of the inorganic particles is preferably 40% by mass or more of the entire composition. The inorganic particles preferably have an average particle size of 0.5 μm or more.

[0009] The viscosity of the organosiloxane is 3 to 18,000 mm 2 / s (25°C). The content of the organosiloxane is preferably less than 20% by mass of the entire composition.

[0010] The organosiloxane is preferably a modified organosiloxane. The modified organosiloxane preferably has at least one selected from the group consisting of a hydrogen atom, an amino group, an ether group, an epoxy group, a mercapto group, a carboxyl group, an acrylic group, a methacryl group, a carboxylic anhydride group, an alkyl group, an aralkyl group, a fluoroalkyl group, a perfluoroalkyl group, an ester group, an amide group, and a phenyl group at any one or all of its side chains, one end, and both ends.

[0011] The modified polyorganosiloxane preferably has at least one selected from the group consisting of a hydrogen atom, an amino group, a carboxyl group, an acrylic group, a carboxylic anhydride group, an alkyl group, a fluoroalkyl group, a perfluoroalkyl group, an ester group, an amide group, and a phenyl group at any one or all of its side chains, one end, and both ends. The modified polyorganosiloxane preferably has at least one selected from the group consisting of a hydrogen atom, an amino group, a carboxyl group, an acryl group, a fluoroalkyl group, a phenyl group, and a carboxylic anhydride group at either its side chain, one end, or both ends.

[0012] The present disclosure also relates to a sheet made of the moisture absorption suppressing composition described above. The sheet of the present disclosure preferably exhibits an increase in moisture content of 60 ppm or less when stored for 24 hours in an environment of 30° C. and 90% RH. The sheet of the present disclosure preferably has a dielectric loss tangent that increases by 30% or less when stored for 24 hours in an environment of 30° C. and 90% RH. The sheet of the present disclosure preferably has a coefficient of linear expansion (CTE) of 200 ppm / K or less.

[0013] The present disclosure also relates to a method for producing the above-mentioned sheet, which is characterized by molding a composition in which fluororesin particles, inorganic particles, and organosiloxane are mixed. In the method for producing the sheet, it is preferable to form the sheet using a composition substantially consisting of fluororesin particles, inorganic particles, and organosiloxane.

[0014] The present disclosure also relates to a metal clad laminate having a metal layer and the above-mentioned sheet as essential layers. The sheet included in the metal clad laminate may contain at least one selected from the group consisting of formaldehyde, formic acid, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane. The metal layer is preferably a copper foil. The present disclosure also relates to a circuit board comprising the above-mentioned metal clad laminate in which the metal layer is a copper foil. Effect of the Invention

[0015] The present disclosure makes it possible to provide a composition that suppresses water and moisture absorption. In particular, a sheet obtained from the water and moisture absorption suppressing composition containing a fluororesin of the present disclosure has excellent performance in that it can suppress poor appearance and changes in properties caused by water absorption, and also suppresses an increase in dielectric tangent caused by moisture absorption. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present disclosure will be described in detail below. Many studies have been conducted on compositions in which fillers such as inorganic particles are blended with fluororesins or other resins. However, for example, a sheet used for a circuit board or the like, which is manufactured from a composition containing inorganic particles, may have problems such as poor appearance and changes in characteristics, particularly an increase in the dielectric tangent of the sheet, due to the water absorption and hygroscopicity caused by the incorporation of inorganic particles.

[0017] In other applications, sheets, lenses, and sealing materials produced from compositions containing inorganic particles may have problems such as changes in light diffusion properties due to dimensional changes in light diffusion sheets, changes in refractive index in lenses, and peeling due to dimensional changes in sealing materials, due to the moisture absorption caused by the incorporation of inorganic particles.

[0018] The present disclosure makes it possible to provide a sheet in which an increase in dielectric tangent is suppressed under high humidity conditions, a light diffusion sheet in which light diffusion properties do not change, a lens in which a change in refractive index is small, and a composition for obtaining an encapsulating material with excellent dimensional stability.

[0019] The composition of the present disclosure is characterized in that inorganic particles and organosiloxane are blended as essential components in a resin. By adding the organosiloxane, water absorption and moisture absorption are suppressed, and a composition capable of reducing changes due to water absorption and moisture absorption is provided.

[0020] The shape of the molded article made of the composition of the present disclosure may be a sheet, a lens, an encapsulant, etc. Also, the composition of the present disclosure may be a laminate in which a part of the layer is the composition of the present disclosure. Also, the composition may be molded into these shapes by a curing reaction from a liquid state.

[0021] Water absorption indicates the degree of adsorption of water molecules that have become clusters through hydrogen bonds, while hygroscopicity is determined by the degree of adsorption of water molecules (water vapor). In the past, there was a demand for suppressing water absorption, but no specific mention was made of hygroscopicity. Water absorption is the effect on liquid water, and even if water absorption can be suppressed, it cannot be said that the effect of water vapor has been suppressed. The sheet of the present disclosure has low water absorption as well as low hygroscopicity.

[0022] The composition of the present disclosure is characterized by containing a fluororesin, inorganic particles, and an organosiloxane. That is, the composition of the present disclosure is characterized by blending an organosiloxane with a fluororesin together with inorganic particles. The mechanism by which the addition of organosiloxane suppresses poor appearance due to water absorption and the mechanism by which the increase in dielectric tangent due to moisture absorption is suppressed has not yet been specifically elucidated, but it is thought that in sheets containing fluororesin and inorganic particles, moisture absorption occurs when water vapor is adsorbed into the gaps between the inorganic particles and the fluororesin, which is the matrix resin, and that by mixing an organosiloxane, which has low surface tension, with the fluororesin and inorganic particles to form a composition, the organosiloxane spreads on the inorganic particle surfaces (void surfaces), and a sheet made of this composition prevents water vapor from penetrating into the sheet and prevents the sheet surface from adsorbing water vapor and even clustered water molecules. In this way, it is believed that the sheet made of the composition of the present disclosure is less likely to absorb water or moisture, and therefore poor appearance and changes in properties, particularly an increase in dielectric tangent, are also suppressed.

[0023] (Organosiloxane) As used in this disclosure, organosiloxane is a compound having a Si-O-Si bond (siloxane bond) in which organic substituents are bonded to silicon. The organosiloxanes used in the present disclosure may be oligomeric or polymeric. Representative examples of the organosiloxane include compounds in which a methyl group is bonded to silicon. In the present disclosure, dimethylpolysiloxane in which all of the side chains and terminals are methyl groups is preferably used, and among these, linear dimethylpolysiloxane is preferred. In addition, volatile organosiloxanes are not suitable for the present disclosure. For example, hexamethyldisiloxane, decamethylcyclopentasiloxane, etc. are listed. These volatilize when the sheet is heated to 300°C or higher, and the effects of the present disclosure cannot be expected.

[0024] In addition, in the present disclosure, it is preferable to use a modified organosiloxane in which some of the methyl groups of the dimethylpolysiloxane are modified with hydrogen atoms or various organic groups. By using the modified organosiloxane, it is expected that the increase in the dielectric tangent due to moisture absorption in the sheet can be suppressed, and decomposition during firing and the amount of gas generated can be suppressed.

[0025] The organosiloxane used in the present disclosure is preferably a liquid, and its viscosity is 3 to 18,000 mm. 2 When the viscosity of the organosiloxane is in the above range, it is preferable in that it is easy to mix and has a high effect of suppressing moisture absorption. The lower limit of the viscosity of organosiloxane is 5 mm. 2 / s (25°C), and more preferably 10 mm 2 / s (25°C), more preferably 20 mm 2 / s (25°C). The upper limit of the viscosity of the organosiloxane is 10,000 mm 2 / s (25°C), and more preferably 5000 mm 2 / s (25°C), and more preferably 2000 mm 2 / s (25°C) is most preferred.

[0026] In this disclosure, the viscosity of the organosiloxane is a value measured at 25° C. using an Ubbelohde viscometer. When two or more types of organosiloxanes are used in combination, the viscosity at 25° C. means the viscosity of the mixture.

[0027] The modified organosiloxane may be one in which an organic group other than a hydrogen atom or a methyl group (hereinafter, sometimes referred to as an organic group, etc.) is introduced into either or all of its side chain, one end, and both ends. For example, one in which an organic group, etc. is introduced into a part of the side chain of the organosiloxane, one in which an organic group, etc. is introduced into one end of the organosiloxane, one in which an organic group, etc. is introduced into both ends of the organosiloxane, one in which an organic group, etc. is introduced into a part of the side chain and both ends of the organosiloxane, etc. may be introduced, and may be appropriately selected and used. Among these, from the viewpoint of suppressing the rate of increase in the dielectric loss tangent, those in which an organic group or the like is introduced into a part of the side chain are preferred.

[0028] In the present disclosure, "having hydrogen atoms at any one or all of its side chains, one terminal, and both terminals" means that a single hydrogen atom is present at any one or all of its side chains, one terminal, and both terminals, rather than a hydrogen atom present in an organic group.

[0029] The modified organosiloxane may be of either a reactive type or a non-reactive type. The organosiloxane used in the present disclosure does not include silane coupling agents used for coating inorganic particles, which will be described later. Specifically, organosiloxanes having an alkoxy group (-OR (R has 1 to 6 carbon atoms), a hydroxyl group, or a halogen group such as a chloro group are not included in the organosiloxane used in the present disclosure.

[0030] Specific examples of the organic group include a carboxyl group, an amino group, an ether group, an epoxy group, a mercapto group, an acrylic group, a methacrylic group, a carbonyl group, a carboxylic anhydride group, an alkyl group other than a methyl group, an aralkyl group, a fluoroalkyl group, a perfluoroalkyl group, an aryl group, an ester group, and an amide group, or a substituent containing any of these.

[0031] Examples of the alkyl group other than the methyl group include alkyl groups having 1 to 6 carbon atoms, such as ethyl, n-propyl, iso-propyl, n-butyl, sec-butyl, iso-butyl, tert-butyl, n-pentyl, and n-hexyl, and preferably n-butyl, n-pentyl, and n-hexyl. The aryl group includes aryl groups having 6 to 10 carbon atoms, such as phenyl and naphthyl, and is preferably a phenyl group. The above fluoroalkyl group and perfluoroalkyl group are linear or branched fluoroalkyl groups or perfluoroalkyl groups having 1 to 50 carbon atoms, and may contain an ether bond. Preferably, it is a linear or branched fluoroalkyl or perfluoroalkyl group having 1 to 40 carbon atoms, which may contain an ether bond. More preferably, it is a linear or branched fluoroalkyl or perfluoroalkyl group having 1 to 30 carbon atoms, which may contain an ether bond. Particularly preferably, it is a linear fluoroalkyl or perfluoroalkyl group having 1 to 20 carbon atoms, which may contain an ether bond.

[0032] The modified organosiloxane used in the present disclosure preferably has at least one selected from the group consisting of a hydrogen atom, an amino group, an ether group, an epoxy group, a mercapto group, a carboxyl group, an acrylic group, a methacrylic group, a carboxylic anhydride group, an alkyl group other than a methyl group, an aralkyl group, a fluoroalkyl group, a perfluoroalkyl group, an aryl group, an ester group, an amide group, and a phenyl group, at either or all of its side chains, one end, and both ends.

[0033] The modified organosiloxane used in the present disclosure more preferably has at least one group selected from the group consisting of a hydrogen atom, an amino group, a carboxyl group, an acrylic group, a carboxylic anhydride group, an alkyl group, a fluoroalkyl group, a perfluoroalkyl group, an ester group, an amide group, and a phenyl group at either or all of its side chains, one end, and both ends.

[0034] The modified organosiloxane used in the present disclosure more preferably has at least one group selected from the group consisting of a hydrogen atom, an amino group, a carboxyl group, an acryl group, a fluoroalkyl group, a phenyl group, and a carboxylic anhydride group, at either its side chain, one end, or both ends.

[0035] Specific examples of modified organosiloxanes include methylhydrogenpolysiloxane, methylphenylpolysiloxane which is a copolymer of dimethylsiloxane and diphenylsiloxane, carboxyl-modified polysiloxane, amino-modified polysiloxane, acrylic-modified polysiloxane, methacryl-modified polysiloxane, fluoroalkyl group-modified polysiloxane, carboxylic anhydride-modified polysiloxane, polyether-modified polysiloxane, epoxy-modified polysiloxane, and epoxy-polyether-modified polysiloxane.

[0036] The polyether in the polyether-modified polysiloxane is preferably a polyalkylene glycol, and examples of the polyalkylene glycol include polyethylene glycol, polypropylene glycol, polytrimethylene glycol, polytetramethylene glycol, polyhexamethylene glycol, and polyalkylene glycols derived from block or random copolymers of ethylene oxide and propylene oxide.

[0037] As the organosiloxane used in the present disclosure, polydimethylsiloxane (KF-96, etc.), methylphenylpolysiloxane (KF-50, etc.), methylhydrogenpolysiloxane (KF-99), carboxyl group-modified polysiloxane (X-22-3701E, X-22-162C, etc.), amino group-modified polysiloxane (KF-868, KF-8012, KF-8008, etc.), acid anhydride-modified polysiloxane (X-22-168, etc.), acrylic-modified polysiloxane (X-22-2445, etc.), fluoroalkyl-modified polysiloxane (X-22-822, etc.), mercapto group-modified polysiloxane (X-22-167B, etc.) (all from Shin-Etsu Chemical Co., Ltd.) and the like are commercially available. Other examples include WACKER AF98 / 1000, WACKER L655, and WACKER FINISH WT1270 manufactured by Wacker Asahi Kasei Silicone, and TSF4704 manufactured by Momentive.

[0038] In the present disclosure, as the organosiloxane, dimethylpolysiloxane, methylhydrogenpolysiloxane, methylphenylpolysiloxane, carboxyl-modified polysiloxane, amino-modified polysiloxane, acrylic-modified polysiloxane, carboxylic anhydride-modified polysiloxane, fluoroalkyl group-modified polysiloxane, and the like can be suitably used.

[0039] The organosiloxane is preferably contained in an amount of less than 20% by mass of the entire composition. By using such an amount, the increase in the dielectric tangent due to moisture absorption in the sheet is well suppressed, and as a result, the dielectric tangent of the sheet can be lowered and the linear expansion coefficient can also be lowered. The amount is more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 2% by mass or less. On the other hand, the lower limit of the amount of the organosiloxane is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, even more preferably 0.05% by mass or more, and particularly preferably 0.2% by mass or more. By using such an amount, the increase in the dielectric tangent due to moisture absorption in the sheet is well suppressed. Note that, when the organosiloxane is contained in an amount of 20% by mass or more of the entire composition, the dielectric tangent and linear expansion coefficient of the sheet tend to be large.

[0040] (Inorganic particles) In the present disclosure, the inorganic particles used are not particularly limited, and examples thereof include one or more selected from silica, ceramics, talc, mica, aluminum oxide, zinc oxide, tin oxide, titanium oxide, calcium carbonate, calcium oxide, magnesium oxide, potassium titanate, glass fiber, glass chips, glass beads, silicon carbide, calcium fluoride, boron nitride, barium sulfate, molybdenum disulfide, and potassium carbonate whiskers. Two or more of these may be used in combination.

[0041] In order to obtain a sheet in which the increase in dielectric tangent due to moisture absorption is suppressed, which is one of the objects of the present disclosure, the use of silica as an essential component is preferable in that it can reduce the relative dielectric constant and the dielectric tangent, and also the linear expansion coefficient. Therefore, in the present disclosure, it is preferable that the inorganic particles used contain silica as an essential component. When silica is used, the silica surface is Si-O-Si-O, and organosiloxane also has Si-O-Si-O bonds in its main skeleton, so it has higher compatibility with organosiloxane than other inorganic particles, and the combination of silica and organosiloxane provides a greater moisture absorption suppression effect.

[0042] The silica content in the inorganic particles is preferably 50% by mass or more, more preferably 65% ​​by mass or more, and even more preferably 80% by mass or more. The content of silica in the inorganic particles in the above range is advantageous in that the dielectric loss tangent can be reduced. The inorganic particles may be composed of silica alone.

[0043] The shape of the inorganic particles is not particularly limited, but is particularly preferably spherical, which is preferable in that it is easy to process uniformly during drilling and has a small specific surface area and therefore low transmission loss. The silica used is preferably spherical silica particles.

[0044] The spherical inorganic particles refer to particles whose particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is calculated by taking a photograph with an SEM and calculating the value from the area and perimeter of the observed particle as (sphericity) = {4π x (area) ÷ (perimeter) 2}. The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.

[0045] The inorganic particles used in the present disclosure preferably have a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is calculated from the smallest particle size. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). It is more preferable that the D50 is 5 μm or less. Since it is possible for small inorganic particles to enter the gaps between large inorganic particles, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a high frequency on the small particle size side compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. Since coarse particles make it difficult to form a thin sheet, it is preferable that coarse particles having a particle size larger than a certain size are removed by a filter or the like.

[0046] The inorganic particles preferably have a water absorption of 1.0% or less, more preferably 0.5% or less. If the water absorption of the inorganic particles is within the above range, the sheet can be prevented from absorbing moisture, and thus a sheet can be obtained in which an increase in dielectric tangent due to moisture absorption is prevented. The water absorption of inorganic particles is based on the mass of the inorganic particles when dry. Water absorption is measured by leaving a dry sample at 40°C and 80% RH for 1 hour, and measuring the water content generated by heating to 200°C using a Karl Fischer moisture meter, and then calculating the water absorption.

[0047] The inorganic particles preferably have an average particle size of 0.5 μm or more. The average particle size here is the D50 value measured by a laser analysis particle size distribution analyzer. If the average particle size is less than 0.5 μm, the inorganic particles may aggregate, making it difficult to obtain a sufficient effect. Furthermore, the upper limit of the average particle size is not particularly limited, but is preferably 250 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less.

[0048] The dielectric loss tangent of the silica at 10 GHz is preferably 0.0025 or less. This value is preferable because the sheet has low loss. The upper limit is more preferably 0.002, even more preferably 0.0015, and most preferably 0.0010. On the other hand, the lower limit of the dielectric tangent is preferably 0.00001.

[0049] In this disclosure, the dielectric loss tangent of silica measured at 10 GHz was measured using a cylindrical cavity resonator and a network analyzer, with a filler powder sample filled in a quartz tube and loaded into the resonator. The characteristics of the resonator (resonant frequency and Q value) were obtained before and after inserting the sample, and the dielectric loss tangent was calculated from the results. This measurement method complies with the Japanese Industrial Standard JIS2565 Microwave Ferrite Core Test Method, and measurements were performed in an environment with a room temperature of 25°C and a humidity of 40%.

[0050] Alternatively, the inorganic particles can be measured for each of the parameters by heating the sheet at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin and extracting the inorganic particles.

[0051] The inorganic particles are preferably surface-treated. By previously subjecting the inorganic particles to a surface treatment, aggregation of the inorganic particles can be suppressed, and the inorganic particles can be favorably dispersed in the resin composition. It is also preferable in that the linear expansion coefficient can be reduced.

[0052] The surface treatment is not particularly limited, and any known surface treatment can be used.Specific examples include treatment with a silane coupling agent such as epoxysilane, aminosilane, isocyanatesilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.

[0053] Among these, it is preferable to use one in which the surface is treated with a silane coupling agent and the inorganic particles are coated with the silane coupling agent. Coating with a silane coupling agent is advantageous in that it can lower the dielectric tangent.

[0054] Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, isocyanate silanes such as 3-isocyanatepropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane.

[0055] The inorganic particles of the present disclosure are preferably surface-treated with a silane coupling agent in an amount of 0.05 to 30% by mass based on the inorganic particles. The surface treatment is not particularly limited and can be carried out by any known method. Specifically, for example, the surface treatment can be carried out by treating the inorganic particles with a silane coupling agent in a solution state in which the silane coupling agent is dissolved in a solvent, or in a solvent-free state.

[0056] The spherical silica particles may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), and Admafuse (manufactured by Admatechs Co., Ltd.).

[0057] The inorganic particles are preferably contained in a proportion of 40% by mass or more of the entire composition. This is preferable in that it provides low thermal expansion while maintaining a low dielectric constant and low loss. It also provides a composition with excellent moldability. The amount is more preferably 50% by mass or more, and even more preferably 55% by mass or more. There is no particular upper limit to the amount of inorganic particles, but it is preferably 80% by mass or less, and even more preferably 70% by mass or less.

[0058] (Fluorine resin) Since fluororesin has low dielectric properties, it can be suitably used for obtaining a sheet in which the increase in dielectric tangent due to moisture absorption is suppressed, which is one of the objects of the present disclosure. Therefore, for such purpose, it is preferable that the composition of the present disclosure contains a fluororesin.

[0059] The fluororesin that can be used in the present disclosure is not particularly limited, and examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene [CTFE] copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], tetrafluoroethylene having a molecular weight of 300,000 or less [LMW-PTFE], etc. These may be used alone or in combination of two or more.

[0060] In particular, perfluoro-based fluororesin is preferable. Among them, polytetrafluoroethylene resin (PTFE) is particularly preferable from the viewpoint of low dielectric properties. PTFE having fibrillation properties is preferable. PTFE having fibrillation properties means PTFE that can be paste-extruded from unsintered polymer powder.

[0061] PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), homopolytetrafluoroethylene (hereinafter referred to as homoPTFE), or a mixture of modified PTFE and homoPTFE. From the viewpoint of maintaining good moldability of polytetrafluoroethylene, the content of modified PTFE in the polymeric PTFE is preferably 10% by weight or more and 98% by weight or less, and more preferably 50% by weight or more and 95% by weight or less. The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.

[0062] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE may be, but is not limited to, one that is uniformly modified by the modified monomer, one that is modified at the beginning of the polymerization reaction, one that is modified at the end of the polymerization reaction, etc. The modified PTFE is preferably a TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE within a range that does not significantly impair the properties of the TFE homopolymer. The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.

[0063] The modified PTFE contains TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500% by weight, more preferably 0.01 to 0.30% by weight, of the total monomer units. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.

[0064] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.

[0065] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF2 = CF-ORf (1) (In the formula, Rf represents a perfluoro organic group.)

[0066] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0067] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE) in which Rf in the above general formula (1) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group. Preferred examples of PAVE include perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).

[0068] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.

[0069] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.

[0070] The fluororesin is preferably non-melt processable. Non-melt processable means that the resin does not have sufficient fluidity even when heated to the melting point or higher, and cannot be molded by a melt molding method generally used for resins. PTFE corresponds to this.

[0071] In the present disclosure, it is preferable to use such a non-melt-processable fluororesin and form it into a sheet by a molding method that fibrillates it. The molding method will be described later.

[0072] The PTFE preferably has an SSG of 2.0 to 2.3. When such a PTFE is used, a PTFE membrane having high strength (cohesion and puncture strength per unit thickness) is easily obtained. Since a PTFE having a large molecular weight has a long molecular chain, it is difficult to form a structure in which the molecular chains are regularly arranged. In this case, the length of the amorphous part increases, and the degree of entanglement between the molecules increases. When the degree of entanglement between the molecules is high, the PTFE membrane is unlikely to deform under an applied load and is considered to exhibit excellent mechanical strength. In addition, when a PTFE having a large molecular weight is used, a PTFE membrane having a small average pore size is easily obtained.

[0073] The lower limit of the SSG is more preferably 2.05, and even more preferably 2.1.The upper limit of the SSG is more preferably 2.25, and even more preferably 2.2.

[0074] Standard specific gravity (SSG) was measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.

[0075] In the present disclosure, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE powder is preferably in the range of, for example, 2 million to 12 million. The lower limit of the molecular weight of the PTFE may be 3 million or 4 million. The upper limit of the molecular weight of the PTFE may be 10 million.

[0076] The number average molecular weight of PTFE can be measured by a method based on standard specific gravity and a method based on dynamic viscoelasticity when melted. The method based on standard specific gravity can be performed by a water displacement method based on ASTM D-792 using a sample molded based on ASTM D-4895 98. The method based on dynamic viscoelasticity is described, for example, by S. Wu in Polymer Engineering & Science, 1988, Vol. 28, 538 and the same document, 1989, Vol. 29, 273.

[0077] The PTFE preferably has a refractive index in the range of 1.2 to 1.6. By having such a refractive index, it is preferable in terms of low dielectric constant. The refractive index can be adjusted to be within the above range by a method of adjusting the polarizability or flexibility of the main chain. The lower limit of the refractive index is more preferably 1.25, more preferably 1.30, and most preferably 1.32. The upper limit of the refractive index is more preferably 1.55, more preferably 1.50, and most preferably 1.45.

[0078] The refractive indexes are values ​​measured using a refractometer (Abbemat 300).

[0079] The PTFE preferably has a maximum endothermic peak temperature (crystalline melting point) of 340±7°C.

[0080] The PTFE may be a low-melting-point PTFE having a maximum peak temperature of 338°C or lower on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter, or a high-melting-point PTFE having a maximum peak temperature of 342°C or higher on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter.

[0081] The low melting point PTFE powder is a powder produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.08 to 2.2, and a dielectric tangent (tan δ) of 1.9×10 -4 ~4.0×10 -4 Examples of commercially available products include Polyflon fine powders F201, F203, F205, F301, and F302 manufactured by Daikin Industries, Ltd., CD090 and CD076 manufactured by Asahi Glass Co., Ltd., and TF6C, TF62, and TF40 manufactured by DuPont.

[0082] The high melting point PTFE powder is also a powder produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tan δ) of 1.6×10 -4 ~2.2×10 -4 As commercially available products, for example, Polyflon fine powder F104 and F106 manufactured by Daikin Industries, Ltd., CD1, CD141, and CD123 manufactured by Asahi Glass Co., Ltd., and TF6 and TF65 manufactured by DuPont can be mentioned.

[0083] The powder in which both PTFE polymer particles are secondary aggregated usually has an average particle size of 250 to 2000 μm. In particular, granulated powder obtained by granulation using a solvent is preferred from the viewpoint of improving the flowability when filling a mold during preforming.

[0084] Powdered PTFE that satisfies the above-mentioned parameters can be obtained by a conventional manufacturing method, for example, by following the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.

[0085] (Resins other than fluororesins) The composition of the present disclosure may use a resin other than a fluororesin as the resin. Examples of resins other than fluororesin include cellulose triacetate film, cycloolefin polymer, cycloolefin copolymer, polyethylene terephthalate, polyethylene naphthalate, polycarbonate, transparent polyimide, thermoplastic polyimide, polyacrylate, polymethyl methacrylate, polystyrene, polyvinyl chloride, syndiotactic polystyrene, polymethylpentene, epoxy resin, alicyclic epoxy resin, silicone resin (excluding those included in the above organosiloxane), polyphenylene ether, modified polyphenylene ether, polyurethane, phenolic resin, bismaleimide resin, cyanate resin, urea resin, melamine resin, unsaturated polyester resin, etc.

[0086] (composition) The composition of the present disclosure contains the above-mentioned organosiloxane, inorganic particles, and a fluororesin or a resin other than a fluororesin. The composition of the present disclosure may contain other components as necessary, but is preferably substantially composed of an organosiloxane, inorganic particles, and a fluororesin or a resin other than a fluororesin, and is particularly preferably composed of an organosiloxane, inorganic particles, and a fluororesin. In the present disclosure, "substantially" means that the amount of fluororesin particles, resins other than fluororesins, inorganic particles, and components other than organosiloxane is 10 mass% or less in the composition. Furthermore, the composition of the present disclosure is preferably composed only of organosiloxane, inorganic particles, and fluororesin or resins other than fluororesin. In particular, it is preferably composed only of organosiloxane, inorganic particles, and fluororesin.

[0087] (Production method of the composition) The composition of the present disclosure can be obtained, for example, by mixing the above-mentioned resin particles, inorganic particles, and organosiloxane components by stirring or the like. The mixing conditions are not particularly specified, but for example, mixing can be performed by stirring at room temperature using a mixer such as a Wonder Crusher. If the stirring time is too short, mixing may be insufficient, and if it is too long, molecular scission or fiberization of the resin may occur, so it is preferable to stir for an appropriate time. In addition, stirring at a low temperature in the presence of dry ice can prevent molecular scission and fiberization of the resin and allow mixing. For example, a composition can be obtained under the following conditions, and a sheet can be obtained from the obtained composition by the sheet manufacturing method described below.

[0088] When producing a sheet by powder rolling molding, it is preferable to weigh out the resin particles, inorganic particles, and organosiloxane components in the desired ratio and stir them with a Wonder Crusher at room temperature for 10 seconds to 10 minutes. Stirring may be performed once or in two or more separate steps.

[0089] When producing a sheet by paste extrusion molding, for example, it is preferable to weigh out the desired amounts of each component, i.e., resin particles, inorganic particles, and organosiloxane, and mix them in a mixer in the presence of dry ice. The temperature during mixing is preferably −10° C. or lower. It is also preferable to add 18 to 23 mass % of an extrusion aid such as oil (IP Solvent 2028) to the obtained mixed powder, mix it, and mature it for about 5 hours.

[0090] (Sheet) The compositions of the present disclosure are suitable for use in forming sheets. The present disclosure also relates to a sheet comprising the above composition.

[0091] The sheet of the present disclosure can suppress water absorption and hygroscopicity. The water absorption rate is preferably 0.1 wt% or less, more preferably 0.08 wt% or less, and most preferably 0.04 wt% or less. The water absorption rate is a value calculated in accordance with IPC TM650 2.6.2.1.

[0092] The sheet of the present disclosure preferably has a moisture content increase of 60 ppm or less when stored for one week under an environment of 30°C and 90% RH. If the moisture content increase is 60 ppm or less, it can be said that moisture absorption is suppressed. The moisture content increase is more preferably 30 ppm or less, and even more preferably 15 ppm or less.

[0093] The above-mentioned increase in moisture content was calculated by measuring the moisture content generated by heating at 250° C. using a Karl Fischer moisture content analyzer.

[0094] The sheet of the present disclosure can also reduce the surface liquid repellency tension. The surface liquid repellency tension can be evaluated by the following method. The sheet was immersed in "Wet Tension Test Mixture" manufactured by Wako Pure Chemical Industries, Ltd. for 1 minute at room temperature, then washed with distilled water, and visually judged whether the wet tension test mixture had penetrated into the sheet. No. 22.6 to 70.0 were used as the wet tension test mixture, and the value of the test liquid with the lowest surface tension among the wet tension test mixtures that did not show any penetration was taken as the critical liquid repellency result. There are different types of mixtures for wetting tension tests, each with a different wetting tension (at 23°C), and each contains a colorant, so that it is possible to visually check whether or not they penetrate into the specimen. The critical liquid repellency tension is preferably 37 mN / M or less, more preferably 32 mN / M, and most preferably 22.6 mN / M.

[0095] The sheet of the present disclosure, particularly when a composition containing a fluororesin is used, is one in which fluctuations in dielectric tangent due to moisture absorption are suppressed. The sheet of the present disclosure preferably has a relative dielectric constant of 3.5 or less at 10 GHz. Having the relative dielectric constant within this range is preferable in terms of low dielectric loss. The upper limit of the relative dielectric constant is more preferably 3.2, and even more preferably 3.1, while the lower limit of the relative dielectric constant is preferably 2.0, and more preferably 2.5.

[0096] The sheet of the present disclosure preferably has a dielectric loss tangent of 0.0015 or less at 10 GHz. By setting the dielectric loss tangent within this range, it is preferable that the loss of electrical signals in the circuit can be suppressed. The dielectric loss tangent is more preferably 0.0012 or less, and even more preferably 0.0011 or less. On the other hand, the lower limit of the dielectric loss tangent is preferably 0.00001.

[0097] The relative permittivity (Dk) and dielectric loss tangent (Df) at 10 GHz of the sheet in this disclosure were determined by measuring Dk and Df at 25°C and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab).

[0098] The sheet of the present disclosure preferably exhibits an increase in dielectric tangent of 30% or less when stored for 24 hours in an environment of 30° C. and 90% RH, more preferably 20% or less, and even more preferably 12% or less.

[0099] The rate of increase in the dielectric tangent was calculated by placing each sample in a thermostatic oven kept at 30° C. and 90% RH, tracking the change in the dielectric tangent after 24 hours, and calculating the rate of increase in the dielectric tangent according to the following formula. Increase rate (%) = (Dielectric tangent after 24 hours - Dielectric tangent before humidity test) / Dielectric tangent before humidity test × 100

[0100] The sheet of the present disclosure preferably has a coefficient of linear expansion (CTE) of 200 ppm / K or less. The above range is preferable in that the sheet has low shrinkage and excellent dimensional stability. The upper limit is more preferably 150 ppm / K, even more preferably 100 ppm / K, and most preferably 70 ppm / K. The lower limit is not particularly limited, but is preferably 10 ppm / K, and more preferably 20 ppm / K.

[0101] The linear expansion coefficient in this disclosure is a value obtained by performing TMA measurement using a TMA-7100 (manufactured by Hitachi High-Tech Science Corporation) in a tensile mode, using a sheet cut to a length of 20 mm, width of 5 mm, and thickness of 150 μm as a sample piece, setting the chuck distance to 10 mm, applying a load of 49 mN, and determining the linear expansion coefficient from the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min.

[0102] In the present disclosure, when a modified organosiloxane is used as the organosiloxane, a sheet can be obtained in which moisture absorption is suppressed and decomposition of the organosiloxane during firing is suppressed.

[0103] The sheet of the present disclosure preferably has a thickness of less than 300 μm. Even if the sheet of the present disclosure is thin, it can fully achieve its purpose. From this viewpoint, it is more preferable that the thickness is less than 200 μm, and even more preferable that the thickness is less than 150 μm. In addition, if the sheet can be processed to a thickness of 100 μm or less as necessary, it is preferable that the sheet can be widely applied to substrates of various thicknesses.

[0104] (Sheet manufacturing method) The sheet of the present disclosure can be obtained by molding a composition in which the above-mentioned resin particles, inorganic particles, and organosiloxane are mixed. Although the manufacturing method is not limited, it is preferable to perform the manufacturing method by, for example, paste extrusion molding, powder rolling molding, etc.

[0105] The present disclosure also relates to a method for producing the above-mentioned sheet, which is characterized by molding a composition in which fluororesin particles, inorganic particles, and organosiloxane are mixed. In the method for producing a sheet according to the present disclosure, it is preferable to use a composition substantially consisting of fluororesin particles, inorganic particles, and organosiloxane for molding.

[0106] As described above, it is preferable to use a non-melt processable fluororesin as the fluororesin used in the sheet of the present disclosure. When such a fluororesin is used and is molded into a sheet, it is preferable to mold the sheet by fibrillating powdered PTFE as a raw material.

[0107] The powdered PTFE preferably has a primary particle size of 0.05 to 10 μm. The use of such a powder has the advantage of excellent moldability and dispersibility. The primary particle size here is a value measured in accordance with ASTM D 4895.

[0108] The powdered PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. By containing PTFE having a secondary particle diameter of 500 μm or more within this range, it is advantageous in that a composite sheet with high strength can be produced. By using PTFE with a secondary particle size of 500 μm or more, a composite sheet with lower resistance and excellent toughness can be obtained.

[0109] The lower limit of the secondary particle diameter is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.

[0110] The powdered PTFE has an average primary particle size of preferably 50 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, and particularly preferably 200 nm or more, since this allows the production of a sheet with higher strength and excellent homogeneity. The larger the average primary particle diameter of PTFE, the more suppressed the increase in paste extrusion pressure when the powder is used for paste extrusion molding, and the better the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization process, it is preferably 350 nm.

[0111] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, measuring the above transmittance for the aqueous dispersion to be measured, and then based on the calibration curve.

[0112] The PTFE used in the present disclosure may have a core-shell structure.The PTFE having a core-shell structure may include, for example, modified polytetrafluoroethylene, which contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in a particle.As such modified polytetrafluoroethylene, for example, the polytetrafluoroethylene described in JP-A-2005-527652 may be included.

[0113] The specific methods for paste extrusion molding and powder rolling molding are not particularly limited, but the general methods are described below.

[0114] (Paste extrusion molding) The method for producing the sheet may include the steps of (1a) mixing the composition containing the fluororesin powder, inorganic particles and organosiloxane obtained by using a hydrocarbon surfactant with an extrusion aid, (1b) paste extrusion molding the mixture obtained, (1c) rolling the extrudate obtained by extrusion molding, (1d) drying the rolled sheet, and (1e) firing the dried sheet to obtain a molded product. The paste extrusion molding can also be carried out by adding conventionally known additives such as pigments to the composition.

[0115] The extrusion aid is not particularly limited, and generally known ones can be used, such as hydrocarbon oils.

[0116] (Powder rolling molding) The sheet can also be formed by powder rolling molding. Powder rolling molding is a method in which a resin powder is fibrillated by applying a shear force to the resin powder, and then molded into a sheet. The method may include a step of subsequently firing the powder to obtain a molded body. More specifically, the composition containing the fluororesin powder, the inorganic particles, and the organosiloxane is mixed while being subjected to a shear force (1) A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. The composition can be obtained by a manufacturing method having the following steps.

[0117] When forming a sheet by such powder rolling molding, it is preferable to mix and mold only the fluororesin powder, inorganic particles, and organosiloxane. The method may further include a step (4) of firing the sheet-like material obtained above at 200 to 400° C. for 1 to 60 minutes. Additionally, step (2) may be omitted.

[0118] The sheet of the present disclosure may also be formed by a casting method in which a solution or dispersion containing a fluororesin, inorganic particles, and organosiloxane is prepared, and then the solution or dispersion is applied onto a substrate and dried.

[0119] In addition, when a baking process is carried out at a temperature of 300° C. or higher during the production of the above-mentioned sheet, if the baking time is within about 30 minutes, for example, the decomposition of the organosiloxane can be limited to a certain extent, and a sheet having the effects of the present disclosure can be obtained.

[0120] (Laminate) The sheet of the present disclosure can be used, for example, as a sheet for a circuit board by laminating it with a metal layer. For example, a metal clad laminate in which a metal layer is bonded to one or both sides of the above-mentioned sheet can be mentioned.

[0121] The present disclosure also relates to a metal clad laminate having a metal layer and the above-mentioned sheet as essential layers. As described above, the sheet containing the fluororesin of the present disclosure can be particularly suitably used in circuit board applications, and can therefore be suitably used as such a metal clad laminate.

[0122] Examples of the metal layer include copper foil, gold foil, silver foil, platinum foil, ruthenium foil, etc. Among these, copper foil is preferred because it has low conductor loss.

[0123] The copper foil preferably has an Rz of 1.6 μm or less. The sheet of the present disclosure also has excellent adhesion to copper foil having a high smoothness of Rz of 1.6 μm or less. Furthermore, the copper foil only needs to have an Rz of 1.6 μm or less on at least the surface that is bonded to the above-mentioned sheet, and the Rz value of the other surface is not particularly limited. The above Rz is the sum of the highest point (maximum peak height: Rp) and the deepest point (maximum valley depth: Rv). The above surface roughness is the ten-point average roughness defined in JIS-B0601. In this specification, the above Rz is a value measured using a surface roughness meter (product name: Surfcom 470A, manufactured by Tokyo Seiki Co., Ltd.) with a measurement length of 4 mm.

[0124] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm, and even more preferably in the range of 9 to 35 μm.

[0125] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.

[0126] The copper foil having Rz of 1.6 μm or less is not particularly limited, and commercially available products can be used. Examples of commercially available copper foil having Rz of 1.6 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.).

[0127] The copper foil may be surface-treated to enhance the adhesive strength with the sheet of the present disclosure.

[0128] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, a UV treatment, an electron beam treatment, etc., and the reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate, it is preferable to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but may be an alkoxy group such as a methoxy group or an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.

[0129] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.

[0130] The copper foil may have a roughening treatment layer on the surface thereof in order to enhance adhesion to the sheet. In addition, if there is a risk that the roughening treatment will degrade the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface can be reduced as necessary, or the roughening treatment can be omitted.

[0131] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.

[0132] The metal clad laminate of the present disclosure may further include layers other than the metal layer and the sheet of the present disclosure. The layers other than the metal layer and the sheet are preferably layers made of at least one material selected from the group consisting of polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, and polybutadiene.

[0133] The layers other than the metal layer and the sheet are not particularly limited as long as they are made of the above-mentioned resins. The thickness of the layers other than the metal layer and the sheet is preferably within the range of 12.5 to 260 μm.

[0134] In the metal clad laminate of the present disclosure, the metal layer may be formed on one or both sides of the sheet. Methods for forming the metal layer include a method for laminating (adhering) a metal layer on the surface of a roll sheet, a vapor deposition method, a plating method, and the like. Methods for laminating the metal layer include a method using heat pressing. The heat pressing temperature may be from the melting point of the sheet -150°C to the melting point of the sheet +40°C. The heat pressing time is, for example, 1 to 30 minutes. The heat pressing pressure may be 0.1 to 10 MPa, and the laminate may be manufactured by such a method.

[0135] The sheet contained in the metal clad laminate of the present disclosure may contain at least one selected from the group consisting of formaldehyde, formic acid, and hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane. When manufacturing the metal clad laminate, the processing temperature is 300° C. or higher, causing decomposition of the organosiloxane contained in the sheet. When the organosiloxane is decomposed, formaldehyde, formic acid, and hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane derived from the organic group of the organosiloxane are generated, so that the sheet contained in the metal clad laminate contains at least one selected from the group consisting of formaldehyde, formic acid, and hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane.

[0136] In the present disclosure, the presence of formaldehyde, formic acid, and hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane in the sheet contained in the metal clad laminate can be confirmed by a method in which the sheet is heated at 360°C, the evolved gas is collected, and the gas is analyzed by thermal desorption GCMS.

[0137] When a sheet contained in a metal clad laminate contains, for example, 50 ppm or more of formaldehyde, formic acid, and at least one selected from the group consisting of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane, it can be said that the sheet used in producing the metal clad laminate contained an organosiloxane.

[0138] The use of the metal clad laminate of the present disclosure is not particularly limited, and it is suitably used as a circuit board. The present disclosure also relates to a circuit board having the above-mentioned metal clad laminate. A circuit board is a plate-shaped component for electrically connecting electronic components such as semiconductors and capacitor chips and simultaneously arranging and fixing them in a limited space. There is no particular limitation on the configuration of the circuit board formed from the metal clad laminate of the present disclosure. The circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The circuit board may be any of a single-sided board, a double-sided board, and a multilayer board (such as a built-up board). In particular, it can be suitably used for flexible boards and rigid boards. In particular, it can be suitably used as a high-frequency printed board of 10 GHz or more.

[0139] In this disclosure, the high-frequency circuit does not only refer to a circuit that transmits only high-frequency signals, but also includes a circuit that has a transmission line that converts a high-frequency signal into a low-frequency signal and outputs the generated low-frequency signal to the outside, a transmission line for supplying power to drive high-frequency compatible components, and other transmission lines that transmit signals other than high-frequency signals, which are arranged on the same plane.The circuit can also be used as a circuit board for an antenna, a filter, etc. The present disclosure also relates to an antenna formed from the circuit board, and is particularly suitable as a millimeter wave antenna for mobility such as automobiles and aircraft.

[0140] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal clad laminate.

[0141] The sheet and metal clad laminate of the present disclosure are used as electric and electronic components, for example, antennas used in electronic devices and communication devices such as ETC, GPS, wireless LAN, and mobile phones, high-speed transmission connectors, CPU sockets, millimeter wave and quasi-millimeter wave radars such as collision prevention radars, RFID tags, capacitors, inverter parts, cable covering materials, insulating materials for secondary batteries such as lithium ion batteries, speaker diaphragms, etc.

[0142] Examples of high-speed communication-compatible substrates include base station antenna substrates, antenna distribution substrates, substrates for RRH (Remote Radio Head) which is the wireless part of a wireless base station, substrates for the control unit or baseband unit (BBU: Base Band Unit) of a wireless base station, transceiver substrates for high-speed communication, substrates for RNC (Radio Network Controller), substrates for high-speed transmitters, substrates for high-speed receivers, substrates for high-speed signal multiplexing circuits, substrates for WiFig using the 60 GHz band, substrates for data transfer used in servers for data centers, etc. Examples of high-speed communication-compatible substrates include antenna substrates, for example, substrates for massive multi-element antennas (Massive MIMO) for large-capacity communication required by standards after 5G. Further, examples include receiving antennas for space-transmission wireless power supply using microwaves. The sheet of the present disclosure has good adhesion to unroughened copper foil with low transmission loss, so that when an antenna is obtained by processing a copper-clad laminate containing the sheet of the present disclosure and unroughened copper foil, the gain is improved, making it particularly suitable for antennas.

[0143] The sheet of the present disclosure can be used not only as an insulator for a substrate but also as an insulator for a signal line coating material, for example, as an insulating coating material (e.g., insulating tube) for a waveguide for transmitting high-speed signals, a QSFP cable for a high-speed LAN, a coaxial cable for high-speed communication (e.g., SFP+ cable, QSFP+ cable, etc.), a coaxial cable for low loss, etc.

[0144] When using such high frequencies, materials used in electrical components such as connectors and communication devices such as casings are required to have stable electrical properties such as low relative dielectric constant (εr) and low dielectric tangent (tanδ). The sheet of the present disclosure can also be used as an insulating material for such materials.

[0145] The sheet of the present disclosure can also be used as an insulating material for connector printed wiring boards that require soldering. The sheet of the present disclosure has excellent heat resistance, so problems are unlikely to occur even at high temperatures during soldering.

[0146] In dielectric waveguides, materials with low dielectric loss are required to transmit high-frequency millimeter waves or submillimeter waves with low loss. The sheet of the present disclosure can also be used as an insulating material for dielectric waveguides that transmit millimeter waves, submillimeter waves, etc. Examples of dielectric waveguides include cylindrical dielectric lines, rectangular dielectric lines, elliptical dielectric lines, tubular dielectric lines, image lines, insulator image lines, trapped image lines, rib guides, strip dielectric lines, inverted strip lines, H guides, nonradiative dielectric lines (NRD guides), and the like.

[0147] In this disclosure, mobility refers to all means and methods related to movement and transportation, including automobiles in general, such as private cars, buses, taxis, and trucks, as well as two-wheeled vehicles, such as motorcycles, bicycles, and mopeds, railways, senior cars, and compact personal mobility vehicles for one person.Mobility is not necessarily limited to vehicles that move on the ground, and may also be vehicles that move in the air or underwater.

[0148] The laminate for a circuit board may be a laminate having a copper foil layer, the above-mentioned sheet, and a base layer. The base layer is not particularly limited, and preferably has a fabric layer made of glass fiber and a resin film layer.

[0149] The fabric layer made of glass fibers is a layer made of glass cloth, glass nonwoven fabric, or the like. Commercially available glass cloth can be used, and glass cloth treated with a silane coupling agent is preferable to enhance affinity with the fluororesin. Examples of glass cloth materials include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass, and E glass, S glass, and NE glass are preferable because they are easily available. The weaving method of the fibers may be plain weave or twill weave. The thickness of the glass cloth is usually 5 to 90 μm, and preferably 10 to 75 μm, but it is preferable to use a glass cloth thinner than the fluororesin film to be used.

[0150] The laminate may use a glass nonwoven fabric as a fabric layer made of glass fibers. The glass nonwoven fabric is a fabric in which short glass fibers are fixed with a small amount of a binder compound (resin or inorganic substance), or a fabric in which the shape is maintained by entangling short glass fibers without using a binder compound, and a commercially available product can be used. The diameter of the short glass fibers is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of the binder compound include resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, and inorganic substances such as silica compounds. The amount of the binder compound used is usually 3 to 15 mass % based on the short glass fibers. Examples of the material of the short glass fibers include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, and preferably 100 to 900 μm. In the present disclosure, the thickness of the glass nonwoven fabric refers to a value measured in accordance with JIS P8118:1998 using a digital gauge DG-925 (load 110 grams, face diameter 10 mm) manufactured by Ono Sokki Co., Ltd. In order to increase the affinity with the fluororesin, the glass nonwoven fabric may be treated with a silane coupling agent.

[0151] Most nonwoven glass fabrics have a very high porosity of 80% or more, so it is preferable to use a sheet that is thicker than a sheet made of fluororesin and compress it by pressure.

[0152] The fabric layer made of glass fibers may be a layer in which a glass cloth and a glass nonwoven fabric are laminated together. This allows the properties of each layer to be combined to obtain suitable properties. The fabric layer made of glass fibers may be in the form of a prepreg impregnated with a resin.

[0153] In the above laminate, the glass fiber fabric layer and the sheet may be bonded at the interface, or the glass fiber fabric layer may be partially or entirely impregnated with the sheet. Furthermore, a prepreg may be prepared by impregnating a fabric made of glass fiber with the fluororesin composition. The prepreg thus obtained may be further laminated with the fluororesin sheet of the present disclosure. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the sheet of the present disclosure may be used.

[0154] The resin film used as the substrate layer is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include those containing epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable. The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption rate, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and even more preferably 40 ppm / °C or less. The water absorption rate is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.

[0155] When the metal clad laminate essentially including the above-mentioned sheet and copper foil is laminated with a base layer such as a resin film layer, the sheet layer side of the metal clad laminate can be adhered to the base layer. In this case, the sheet layer side of the metal clad laminate may be surface-treated before lamination to enhance adhesion performance. The surface treatment here is not particularly limited, and examples thereof include the above-mentioned plasma treatment.

[0156] In the above laminate, the order in which the copper foil layer, the base material, and the above-mentioned sheets are laminated and the manufacturing method are not particularly limited, and a layer configuration according to the purpose can be adopted. Specific examples of the above-mentioned lamination order include a base material layer / sheet / copper foil layer, a copper foil layer / sheet / base material layer / sheet / copper foil layer, and a copper foil layer / base material layer / sheet / base material layer / copper foil layer. If necessary, other layers may also be included. EXAMPLES

[0157] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.

[0158] The spherical silica used in each of the examples and comparative examples is as follows. Admatechs SC6500-SQ (Silica A: average particle size 2.1 μm, dielectric tangent 0.00051) Admatechs SC6500-SQ (average particle size 2.1 μm) treated with 3-aminopropyltriethoxysilane at a treatment amount of 0.2% by mass relative to the mass of the silica particles (dielectric tangent 0.00058) Admatechs SC6500-SQ (average particle size 2.1 μm) treated with 3-aminopropyltriethoxysilane at a treatment amount of 1% by mass relative to the mass of the silica particles (dielectric tangent 0.00044) Admatechs SC6500-SQ (average particle size 2.1 μm) treated with 3-isocyanatepropyltriethoxysilane at a treatment amount of 0.2% by mass relative to the mass of the silica particles (dielectric loss tangent 0.00052)

[0159] The crushed silica used in each of the Examples and Comparative Examples is as follows. Tatsumori ZA-30 (Silica B: average particle size 5.6 μm, dielectric tangent 0.00838)

[0160] The organosiloxanes used in the examples and comparative examples are as follows: Shin-Etsu Chemical Co., Ltd. KF-96-50CS (polydimethylsilicone oil: abbreviated as PDMS) Shin-Etsu Chemical Co., Ltd. X-22-162C (polydimethylsilicone oil with both ends modified with RCOOH groups) Shin-Etsu Chemical Co., Ltd. KF-8012 (polydimethylsilicone oil with both ends modified with RNH2 groups) Shin-Etsu Chemical Co., Ltd. X-22-168B (polydimethylsilicone oil with both ends modified with carboxylic anhydride groups) Shin-Etsu Chemical Co., Ltd. X-22-2445 (polydimethylsilicone oil with both ends modified with acrylic groups) Shin-Etsu Chemical Co., Ltd. KF-868 (polydimethylsilicone oil whose side chains are modified with RNH2 groups) Shin-Etsu Chemical Co., Ltd. KF-99 (polydimethylsilicone oil whose side chains are modified with hydrogen atoms) Shin-Etsu Chemical Co., Ltd. KF-50-100CS (polydimethylsilicone oil whose side chains are modified with phenyl groups) Shin-Etsu Chemical Co., Ltd. X-22-822 (polydimethylsilicone oil whose side chains are modified with C2H4CF3 groups)

[0161] The fluororesin particles (PTFE) used in each example had the following properties. Average particle size: 500μm Apparent density: 460g / L Standard specific gravity: 2.17

[0162] (Powder rolling molding) Fluororesin particles (PTFE), silica, and organosiloxane were weighed out in the proportions shown in Tables 1 and 2, and stirred twice for 30 seconds at room temperature with a Wonder Crusher setting of 6. The resulting mixture was rolled with two rolls (roll gap: set to 100 μm, roll temperature: 100° C.) to obtain a sample with a film thickness of 125 μm, and baked at 360° C. for 15 minutes to obtain a sheet.

[0163] (Paste extrusion molding) The fluororesin particles (PTFE), silica, and organosiloxane were weighed out in the prescribed amounts in the ratios shown in Table 1, and mixed in a mixer in the presence of dry ice. The temperature during mixing was -10°C or lower. Oil (IP Solvent 2028) was added at 18-23% to the obtained mixed powder, mixed, and aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed body was extruded at 40°C and 50 mm / min to obtain an extrusion sample. The extrusion sample was rolled with two rolls to obtain a sample with a film thickness of 125 μm, which was then dried at 200°C for 2 hours and calcined at 360°C for 15 minutes to obtain a sheet.

[0164] Each of the obtained samples was evaluated based on the following criteria.

[0165] [Sheet thickness] Measurements were taken using a micrometer.

[0166] [Dielectric constant (Dk) and dissipation factor (Df) of the sheet] The relative dielectric constant and dielectric loss tangent were measured at 25°C and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab).

[0167] [Constant humidity test] Each sample was placed in a constant temperature and humidity oven maintained at 30°C and 90% RH, and the change in dielectric tangent after 24 hours was tracked. The rate of increase was calculated using the following formula. Increase rate (%) = (Dielectric tangent after 24 hours - Dielectric tangent before humidity test) / Dielectric tangent before humidity test × 100

[0168] Coefficient of Linear Expansion (CTE) TMA measurements were performed in tensile mode using a TMA-7100 (Hitachi High-Tech Science Corporation). A sheet cut to a length of 20 mm, width of 5 mm, and thickness of 150 μm was used as a sample piece. The distance between the chucks was set to 10 mm, and the linear expansion coefficient was calculated from the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min while applying a load of 49 mN. The results are shown in Tables 1 and 2.

[0169] [Moisture rise in sheet] Each sample was placed in a thermostatic oven maintained at 30°C and 90% RH for one week. The samples were shredded before and after the humidity test and placed in the vaporization chamber of a moisture measuring device (Mitsubishi Chemical CA-200, VA-200) to analyze the moisture generated at 250°C. The sheet of Comparative Example 1 had a moisture content of 190 ppm before the constant humidity test and 280 ppm after the constant humidity test. The sheet of Example 1 had a moisture content of 240 ppm before the constant humidity test and 220 ppm after the constant humidity test. The significant digits are two.

[0170] [Formaldehyde content in sheets included in metal clad laminates] The sample was cut into approximately 10 mm squares, sealed in a heating vessel, and heated at 360°C for 30 minutes in the presence of N2 gas. The evolved gas was collected in an adsorption tube and subjected to thermal desorption GC / MS measurement (Markes TD-100 and Agilent GC7890A+5875C). A calibration curve was created from the absolute amount of the standard and the obtained peak area value, and quantification was performed. The sheet of Example 5 generated 220 μg / g of gas and contained cyclic siloxane. The sheet of Example 9 generated 110 μg / g of gas and contained cyclic siloxane.

[0171] [Water absorption test] The test was carried out in accordance with IPC-TM-650 test method 2.6.2.1. The water absorption rate was calculated using the following formula:

number

[0172] The sheet of Example 1 had a water absorption rate of 0.021 wt %. The sheet of Comparative Example 1 had a water absorption rate of 0.195 wt %. The sheet of Example 5 had a water absorption rate of 0.022 wt %. The sheet of Example 6 had a water absorption rate of 0.018 wt %.

[0173] [Surface liquid repellency tension test] The sheet was immersed in Wako Pure Chemical Industries' "mixture for wetting tension test" for 1 minute at room temperature, then washed with distilled water and visually judged whether the mixture for wetting tension test had penetrated into the sheet. No. 22.6 to 70.0 were used as the mixture for wetting tension test, and the value of the test liquid with the lowest surface tension among the mixtures for wetting tension test that did not show any penetration was taken as the result of the critical liquid repellency. The sheet of Example 1 had a critical liquid repellent tension of 22.6 mN / M. The sheet of Comparative Example 1 had a critical liquid repellent tension of 22.6 mN / M. The sheets of Comparative Example 1 and Example 1 had the same surface liquid repellency tension, but in terms of water absorption, the sheet of Comparative Example 1 was insufficient. The composition of the present disclosure can also reduce the water absorption.

[0174] [Table 1]

[0175] [Table 2]

[0176] From the above results, the sheet of the present disclosure has excellent performance in terms of suppressing water absorption and moisture absorption under high humidity conditions and suppressing an increase in dielectric tangent. [Industrial Applicability]

[0177] The sheet of the present disclosure can be suitably used in particular for circuit boards, especially for high-frequency printed circuit boards.

Claims

1. A composition comprising a fluororesin, inorganic particles, and an organosiloxane.

2. 2. The composition according to claim 1, wherein the inorganic particles are inorganic particles containing silica as an essential component.

3. 3. The composition according to claim 1, wherein the fluororesin is a perfluororesin.

4. The composition according to claim 3, wherein said perfluoro-based fluororesin is polytetrafluoroethylene.

5. The composition of claim 2, wherein said silica is spherical silica.

6. The composition according to claim 2, wherein the silica has a dielectric loss tangent at 10 GHz of 0.0025 or less.

7. 3. The composition according to claim 1, wherein the inorganic particles are coated with a silane coupling agent.

8. 3. The composition according to claim 1, wherein the content of the inorganic particles is 40% by mass or more of the total composition.

9. 3. The composition according to claim 1, wherein the inorganic particles have an average particle size of 0.5 μm or more.

10. The viscosity of the organosiloxane is 3 to 18,000 mm 2 The composition according to claim 1 or 2, wherein the viscosity is 100% by mass % (25°C).

11. 3. The composition according to claim 1, wherein the content of the organosiloxane is less than 20% by mass of the entire composition.

12. 3. The composition according to claim 1, wherein the organosiloxane is a modified organosiloxane.

13. The composition according to claim 12, wherein the modified organosiloxane has at least one selected from the group consisting of a hydrogen atom, an amino group, an ether group, an epoxy group, a mercapto group, a carboxyl group, an acrylic group, a methacrylic group, a carboxylic anhydride group, an alkyl group, an aralkyl group, a fluoroalkyl group, a perfluoroalkyl group, an ester group, an amide group, and a phenyl group at any one or all of its side chains, one end, and both ends.

14. The composition according to claim 12, wherein the modified organosiloxane has at least one group selected from the group consisting of a hydrogen atom, an amino group, a carboxyl group, an acrylic group, a carboxylic anhydride group, an alkyl group, a fluoroalkyl group, a perfluoroalkyl group, an ester group, an amide group, and a phenyl group at any one or all of its side chains, one end, and both ends.

15. The composition according to claim 12, wherein the modified organosiloxane has at least one group selected from the group consisting of a hydrogen atom, an amino group, a carboxyl group, an acryl group, a fluoroalkyl group, a phenyl group, and a carboxylic anhydride group at any one of a side chain, one terminal, and both terminals thereof.

16. The fluororesin is polytetrafluoroethylene, the inorganic particles are silica, The content of the inorganic particles is 50% by mass or more and 70% by mass or less, the organosiloxane is at least one selected from the group consisting of dimethylpolysiloxane, methylhydrogenpolysiloxane, methylphenylpolysiloxane, carboxyl-modified polysiloxane, amino-modified polysiloxane, acrylic-modified polysiloxane, carboxylic anhydride-modified polysiloxane, and fluoroalkyl group-modified polysiloxane; The composition according to claim 1, wherein the content of the organosiloxane is 0.05% by mass or more and 2% by mass or less.

17. A sheet comprising the composition according to claim 1 or 2.

18. 18. The sheet according to claim 17, which shows an increase in moisture content of 60 ppm or less when stored for one week in an environment of 30° C. and 90% RH.

19. 18. The sheet according to claim 17, which has a dielectric loss tangent increase rate of 30% or less when stored for 24 hours in an environment of 30° C. and 90% RH.

20. 18. The sheet according to claim 17, having a coefficient of linear expansion (CTE) of 200 ppm / K or less.

21. 18. A method for producing the sheet according to claim 17, comprising molding a composition obtained by mixing fluororesin particles, inorganic particles, and organosiloxane.

22. The method for producing a sheet according to claim 21, wherein molding is performed using a composition substantially consisting of fluororesin particles, inorganic particles, and organosiloxane.

23. A metal clad laminate comprising a metal layer and the sheet according to claim 17 as essential layers.

24. 24. The metal clad laminate according to claim 23, wherein the sheet contained in the metal clad laminate contains at least one selected from the group consisting of formaldehyde, formic acid, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane.

25. 24. The metal clad laminate according to claim 23, wherein the metal layer is a copper foil.

26. A circuit board comprising the metal clad laminate according to claim 23.

Citation Information

Patent Citations

  • Filler-containing resin composition and its utilization

    JP2005330401A

  • Curable resin composition, curable resin composition tablet, molded body, semiconductor package, semiconductor component and light emitting diode

    JP2014210843A

  • Water-based coating composition and coated article

    JP2022125043A

  • Liquid crystal polymer film, and laminate

    JP2023013060A

  • Adhesive resin sheet, printed wiring board, and electronic apparatus

    JP2023017308A